Nurses and physicians' perception of the care of oncology patients in the emergency department - Silvana Bastos Cogo; Ariele Priebe Reisdorfer; Jéssica Luíza Beck; Tais Falcão Gomes; Aline Gomes Ilha; Pâmela Barros de Leon; Nara Marilene Oliveira Girardon-Perlini
ABSTRACT Objectives: to understand nurses' and physicians' perceptions of the care of people with cancer admitted to an emergency department of a general hospital. Methods: descriptive study with a qualitative approach. Data collection took place from September to November 2017 through semi-structured interviews in which participated 12 professionals from the emergency department, including nurses and physicians. The data were analyzed using Minayo's operative proposal. Results: three categories emerged: 1) The person with cancer from nurses and physicians' perspective; 2) Comprehensive care of people with cancer or deconfiguration in the emergency department?; and 3) The context of the emergency department and the repercussions on the care of people with cancer. Final Considerations: we identified that the care provided to people with cancer in the emergency department is carried out differently regarding the overall population due to the disease's particularities, which lead us to reflect on the quality and humanization of care.